Inhibition of Accumulation of Neutral Lipids and Their Hydroperoxide Species in Hepatocytes by Bioactive Allium sativum Extract - Dya Fita Dibwe; Saki Oba; Satomi Monde; Shu-Ping Hui (Antioxidants, 2024)
Our ongoing research suggests that extracts from plant-based foods inhibit the accumulation of lipid droplets (LDs) and oxidized lipid droplets (oxLDs) in liver cells. These findings suggest their potential use in the alleviation of metabolic dysfunction-associated fatty liver disease (MAFLD) and its most severe manifestation, metabolic dysfunction-associated steatohepatitis (MASH). Allium extracts (ALs: AL1–AL9) were used to assess their ability to reduce lipid droplet accumulation (LDA) and oxidized lipid droplet accumulation (oxLDA) by inhibiting neutral lipid accumulation and oxidation in LD. Among the tested Allium extracts, AL1, AL3, and AL6 demonstrated substantial inhibitory effects on the LDA. Furthermore, AL1 extract showed real-time inhibition of LDA in HepG2 cells in DMEM supplemented with oleic acid (OA) within 12 h of treatment. Our lipidomic approach was used to quantify the accumulation and inhibition of intracellular triacylglycerol (TAG) and oxidized TAG hydroperoxide [TG (OOH) n = 3] species in hepatocytes under OA and linoleic acid loading conditions. These results suggest that Allium-based foods inhibit LD accumulation by decreasing intracellular lipids and lipid hydroperoxides in the hepatocytes. The metabolomic analysis of AL1—the bioactive LDAI extract—using both LC-MS/MS and 1D-NMR [1H, 13C, and Dept (135 and 90)] approaches revealed that AL1 contains mainly carbohydrates and glucoside metabolites, including iridoid glucosides, as well as minor amino acids, organosulfur compounds, and organic acids such as the antioxidant ascorbic acid (KA2 = S13), and their derivatives, suggesting that AL1 could be a potential resource for the development of functional foods and in drug discovery targeting MAFLD/MASH and other related diseases.